The Effect of Reporting Streaks on Ex Ante Uncertainty - Neururer, Thaddeus; Papadakis, George; Riedl, Edward J. (Management Science, 2020)
This paper predicts and finds that investor uncertainty surrounding a key information release event—the earnings announcement—is decreasing in a firm’s reporting streak. We use two proxies related to investor ex ante uncertainty and corresponding pricing of such uncertainty: option-implied volatilities and variance risk premiums; both are measured with maturities surrounding the impending quarterly earnings announcement. Consistent with prior research, we measure reporting streak as the number of consecutive quarters the firm meets or beats the consensus analyst earnings-per-share forecast. Empirical results confirm expectations that the two uncertainty-related constructs are decreasing in the length of the reporting streak. These results, combined with further evidence documenting that lower uncertainty leads to lower stock returns surrounding the earnings announcements, suggest that longer reporting streaks reflect lower risk during earnings announcements. This paper was accepted by Shiva Rajgopal, accounting.